A narrative review of natural history, epidemiology and risk factors for hepatitis C infection - Mohd Suan, Mohd Azri; Md Said, Salmiah; Azman, Ahmad Zaid Fattah; Abu Hassan, Muhammad Radzi (Universiti Putra Malaysia Press, 2019)
Hepatitis C infection is a major public health problem that can be dealt with urgent and timely attention. Recently, WHO Global Hepatitis Report showed that 71 million people, equivalent to approximately 1% of the world population, are infected with hepatitis C. The disease incidence, mortality rate and risk factors vary across geographical regions. The virus is transmitted primarily through drug injection and exposure to infected blood products in healthcare and community settings. The common causes of death related to virus infections are decompensated liver cirrhosis and hepatocellular carcinoma. Hepatitis C infection is mainly prevented by identifying and controlling any possible risk factors for virus transmission because treatment is costly and limited in availability. In this review, articles discussing the natural history, epidemiology and risk factors for hepatitis C infection are reviewed.